Groundwater Investigation with Geoelectrical Method in Dulah Laut Village, Tual City - Andrias Izaac Latupapua (Agrologia, 2022)
Groundwater availability in small islands with limestone is generally low. In order determine the availability and quality of groundwater, geoelectrical measurements were carried out with the Schlumberger electrode configuration on two tracks of Dulah Laut 1 and Dulah Laut 2. The results showed that the rock resistivity in Dulah Laut Village ranged from 27.4 – 1561 Ωm. Groundwater at the Dulah Laut 1 and Dulah Laut 2 were found at a depth of 5.21 m and 7.93 m below ground surface, respectively. The groundwater potential zone with resistivity of less than 150 Ωm was found at a depth of 4 m below the  surface. Groundwater quality was classified as moderately polluted with high salinity.